Influence of preliminary irradiation by gamma-quanta on development of catastrophic failures during operation of IR-LEDs; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Gradoboev A. V. Aleksandr Vasilyevich (Radiation physics and chemistry of condensed matter, 2017)
Title screen